Acknowledgements 2025 - Revista de Nutrição (Revista de Nutrição, 2025)
Acknowledgements The articles published in Revista de Nutrição in 2025 were evaluated by ad hoc specialists reviewers: Amanda da Silva Franco | Faculdade Bezerra de Araújo Ana Carolina Alencar Barros | Universidade Federal de Santa Catarina Ana Carolina Barco Leme | Universidade de São Paulo Ana Carolina Bueno | Universidade de São Paulo Ana Laura Brandão | Fundação Osvaldo Cruz Ana Lorena Lima Ferreira | Universidade Federal do Rio de Janeiro Anabelle Retondario | Universidade Federal do Paraná Angélica Barbosa Neres da Mata | Universidade de São Paulo Angélica Cotta Lobo Leite Carneiro | Universidade Federal de Juiz de Fora Antônio Augusto Ferreira Carioca | Universidade de Fortaleza Aylin Bayindir-Gümüs | Ankara University Burcu Merve Aksu | Demiroglu Bilim Universitesi Camila Cremonezi Japur | Universidade de São Paulo Camila Maria de Arruda | Universidade de Marília Carlos Eduardo Ferreira de Moraes | Universidade Federal do Rio de Janeiro Ceren Gezer | Eastern Mediterranean University Daniela Alves Silva | Universidade Federal do Espírito Santo Daniele Botelho Vinholes | Universidade Federal da Ciências da Saúde de Porto Alegre Elif Ede Çintesun | İstanbul Sabahattin Zaim Üniversitesi, Emine Elibol | Universidade Ankara Yildirim Beyazit Emre Batuhan Kenger | Istanbul Bilgi University Felipe de Souza Cardoso | Faculdade Arthur Sá Earp Neto Fernanda Almeida de Oliveira | Universidade de São Paulo Flávia de Conti Cartolano | Universidade de São Paulo Flávia Ramos | Universidade Federal da Fronteira Sul Francisco Romão Ferreira | Universidade do Estado do Rio de Janeiro Gabriela Milhassi Vedovato | Universidade Federal de São Paulo Gloria Maria Almeida Souza Tedrus | Pontíficia Universidade Católica Helder Matheus Alves Fernandes | Universidade Estadual do Ceará Imran Ali | Northumbria University Jasilaine Andrade Passos | Universidade Federal do Recôncavo da Bahia Jéssica Elkfury | Universidade Federal do Rio Grande do Sul Jéssica Nobre | Universidade do Estado do Rio de Janeiro Jéssica Raquim Araújo | Universidade Federal de Minas Gerais Joanna Myszkowska-Ryciak | Warsaw University of Life Sciences Joaquim Huaina Cintra Andrade | Universidade Estadual do Ceará José Anael Neves | Universidade Estadual do Ceará José Anael Neves | Universidade Estadual do Ceará Juarez Pereira Furtado | Universidade Federal de São Paulo Juliana Sicchieri | Universidade de São Paulo Laís Ferreira Dias | Universidade de São Paulo Leandro da Cunha Baia |Universidade de Brasília Liliana Paula Bricarello | Universidade Federal de Santa Catarina Lívia Fernandes de Lima | Universidade de São Paulo Márcia Guimarães Mello Alves | Universidade Federal Fluminense Maria Bárbara Galdino-Silva | Universidade Federal do Ouro Preto Maria Carolina de Lima | Universidade de São Paulo Maria Micheliana da Costa Silva | Universidade de Viçosa Maria Sebastiana Silva | Universidade Federal de Goiás Maria Teresa Iglesias-Lopez | Universidad Francisco de Vitoria Mariele Boscardin | Universidade Federal de Santa Maria Monalisa Nascimento dos Santos Barros | Universidade Estadual do Sudoeste da Bahia Nilce Maria da Silva Campos Costa | Universidade Federal de Goiás Nilce Maria Silva Campos Costa | Universidade Federal de Goiás Patrícia Camacho Dias | Universidade Federal Fluminense Rafaela Karen Fabri | Universidade Federal de Santa Catarina Rafaela Lira Formiga Cavalcanti | Universidade Federal da Paraíba Riceli Rodeghiero Oliveira | Universidade Federal de Pelotas Rubia Daniela Thieme | Universidade Federal do Paraná Sheila de Oliveira Faria | Universidade de São Paulo Tatiana Uchôa Passos | Universidade Estadual do Ceará Vanessa Alves Ferreira | Universidade Federal de Minas Gerais Wan Rosli Wan Ishak | Universiti Sains Malaysla Wanderson Roberto da Silva | Centro Universitário de Patos de Minas